The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12864-020-07118-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-IPMS analysis reveals a tissue-dependent miR156/SPL13 regulatory mechanism in alfalfa drought tolerance

Abstract: Background We previously reported on the interplay between miR156/SPL13 and WD40–1/DFR to improve response to drought stress in alfalfa (Medicago sativa L.). Here we aimed to investigate whether the role of miR156/SPL13 module in drought response is tissue-specific, and to identify SPL13-interacting proteins. We analyzed the global transcript profiles of leaf, stem, and root tissues of one-month old RNAi-silenced SPL13 (SPL13RNAi) alfalfa plants exposed to drought stress and conducted protein-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Among them, we found that miR156 was significantly up-regulated in plants under drought stress. Overexpression of miR156 can increase the levels of abscisic acid and antioxidants in plants [ 38 ] and affect photosynthesis and photorespiration by silencing SPL13, thereby alleviating the damage caused by drought stress [ 39 ]. GO enrichment analysis of its target genes indicated that the terms hormone operation (GO:0,009,914) and transport (GO:0,006,810) were enriched, indicating that our results are consistent with results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, we found that miR156 was significantly up-regulated in plants under drought stress. Overexpression of miR156 can increase the levels of abscisic acid and antioxidants in plants [ 38 ] and affect photosynthesis and photorespiration by silencing SPL13, thereby alleviating the damage caused by drought stress [ 39 ]. GO enrichment analysis of its target genes indicated that the terms hormone operation (GO:0,009,914) and transport (GO:0,006,810) were enriched, indicating that our results are consistent with results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These observations show that the miR156/SPL module may contribute to genetic variability through the regulation of plant development and abiotic stress responses. The phenotypic changes and stress response were similar to those of the miR156-overexpressing alfalfa genotypes, including delayed flowering, reduced stem length, and increased shoot branching, and played a positive role in abiotic stress tolerance [ 14 , 47 , 48 , 49 ]. This observation suggests that the miR156/SPL module is integrated with the plant developmental and stress response.…”
Section: Discussionmentioning
confidence: 86%
“…Identification of these genes can help us better understanding of tissue-gene relationship. In alfalfa, RNA-seq analysis uncovered molecular mechanisms underlying abiotic stress, including salt [ 52 , 53 ], drought [ 54 , 55 ], and cold tolerance [ 56 ]. Meanwhile, pathways involved in early flowering [ 57 ] and differentially expressed genes related to defoliation traits [ 58 ] had also been identified in alfalfa by transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%